STUDI NEUTROFIL PADA PENDERITA DEMAM TIFOID DI RSUD PETALA BUMI PEKANBARU - Darmadi - Adi (Jurnal Sains dan Teknologi Laboratorium Medik, 2021)
Typhoid fever is an acute fever caused by the salmonella bacteria which attacks the digestive tract and other organs of the body. The purpose of this study was to determine the percentage of neutrophil stab and neutrophil segments in patients with typhoid fever with titers 1/320 and to determine the morphology of neutrophil segments in patients with typhoid fever with titers 1/320. The design of this research is descriptive research, a descriptive cross-sectional study. The place and time of the study were carried out at Pekanbaru Petala Bumi General Hospital in December 2018 - June 2019. The samples used were EDTA blood patients with typhoid fever with widal 1/320 titer as many as 10 samples with non probability sampling purposive sampling.The results of this study are Neutrophil stab with a value of 2-6% as many as 2 respondents, and a value of> 6% as many as 8 respondents. Whereas in segment neutrophils with a value of 50-70% as many as 5 respondents and<50% 5 respondents. The conclusion of this study is on acute bacterial infections, Neutrophils Stab (young Neutrophils) has increased which is usually called a leftward shift (Shift to the left).Core neutrophil segment abnormalities such as hypersegmentation usually occur in infections, this hypersegmentation disorder is caused by a disruption of the neutrophil nucleus during infection.